Dynamics of Early Childhood Education in Taiwan: A Comparative Study of Traditional and Innovative Approaches - Damayanti, Erma; Djollong, Andi Fitriani; Asfahani, Asfahani; Sitopu, Joni Wilson; Yadav, Uma Shankar (Absorbent Mind, 2024)
This comparative study delves into the dynamics of early childhood education (ECE) in Taiwan, examining the coexistence and interaction between traditional and innovative pedagogical approaches. Through qualitative research methods, including interviews, focus groups, and participant observations, insights were gathered from key stakeholders in Taiwanese ECE settings. Findings reveal that traditional approaches, rooted in Confucian values, emphasize academic readiness and teacher-directed instruction, while innovative methodologies prioritize holistic development and child-centered learning experiences. Contextual factors such as socio-economic influences and cultural traditions significantly shape the adoption and effectiveness of these approaches. The study underscores the importance of a balanced approach that integrates the strengths of both traditional and innovative methods to optimize early childhood learning experiences. These insights have implications for policy-making, curriculum development, and professional development initiatives to enhance the quality and effectiveness of early childhood education in Taiwan.